2017
DOI: 10.1534/genetics.116.194555
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleoporin Nup2 Contains a Meiotic-Autonomous Region that Promotes the Dynamic Chromosome Events of Meiosis

Abstract: Meiosis is a specialized cellular program required to create haploid gametes from diploid parent cells. Homologous chromosomes pair, synapse, and recombine in a dynamic environment that accommodates gross chromosome reorganization and significant chromosome motion, which are critical for normal chromosome segregation. In Saccharomyces cerevisiae, Ndj1 is a meiotic telomere-associated protein required for physically attaching telomeres to proteins embedded in the nuclear envelope. In this study, we identified a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 107 publications
1
24
0
Order By: Relevance
“…However, the interpretation of these results is complicated by the fact that loss of NDJ1 also causes synapsis defects 53 . As the nonessential nucleoporin Nup2 was recently identified as an interactor of Ndj1 54 , we also analyzed Hop1 in nup2Δ mutants. Intriguingly, Hop1 did not become enriched in the EARs in late prophase in nup2Δ ndt80Δ mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the interpretation of these results is complicated by the fact that loss of NDJ1 also causes synapsis defects 53 . As the nonessential nucleoporin Nup2 was recently identified as an interactor of Ndj1 54 , we also analyzed Hop1 in nup2Δ mutants. Intriguingly, Hop1 did not become enriched in the EARs in late prophase in nup2Δ ndt80Δ mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The nuclear basket nucleoporins Nup1 and Nup60 have innate membrane binding and shaping capabilities, making them attractive candidates to initiate insertion of new NPCs (Mészáros et al, 2015). Indeed, deletion of non-essential nuclear basket nucleoporins results in reduced sporulation efficiency and impaired gamete viability, supporting an important functional role during the meiotic program (Chu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the presence of paired HAS1-TDA1 alleles in the nucleoplasm suggests that such nuclear pore-independent pairing mechanisms may act at HAS1-TDA1 ( Figure 5C and Figure 5—source data 2 ). Interestingly, a recent study showed that Nup2 is involved in meiotic homolog pairing ( Chu et al, 2017 ), suggesting that Nup2 may more generally play a role in homolog pairing.…”
Section: Discussionmentioning
confidence: 99%